THE USE OF VISUAL AIDS IN THE TEACHING OF ACCOUNTING. - Froebe, John A. (The Accounting Review, 1959)
The article focuses on the use of visual aids in the teaching of accounting. In his article, professor J.W. Ruswinckel has explained that there were many advantages in using visual aids in the accounting classroom and there were also some important disadvantages, namely, the time required for preparing the material for photographing and binding films in glass protectors after frames were processed. In the race for competitive position in the photographic industry in the last seven years, manufacturers of cameras, projectors, screens and films have made tremendous improvements in their products. Many accounting departments offer courses in fundamentals of elementary accounting or cost accounting for engineers and other non-accounting majors. Frequently, most members of these classes are advanced students and the pace of the work can be accelerated in comparison with the speed at which the material can be presented to freshmen. The balance sheets, income and other statements of well-known corporations can be used as source material for making slides for illustrating and explaining accounting concepts and, thereby, maintaining a fast tempo in these classes.